2005
DOI: 10.1095/biolreprod.104.035493
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Hormones and Follicular Growth During Development of One or Multiple Dominant Follicles in Cattle1

Abstract: The mechanisms regulating ovulation rate under natural conditions are not yet defined, particularly for monovular species. In the present study, we evaluated ovarian structures (every 12 h by ultrasonography) and circulating hormones (every 6 h) to determine the differences between cows that developed one (single dominant; n = 16), two (double dominant; n = 8), or three (triple dominant; n = 3) dominant follicles. The four largest follicles were tracked retrospectively, and the data were normalized to the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
3
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 46 publications
9
74
3
6
Order By: Relevance
“…This supports the data of practitioners, who report about adequate breeding success in the early post-partum period, if they breed only cows which show a good heat in that usually nonrecommended time (Beetz 2012). But these results are in contrast to other studies, which identified low follicle (Lopez et al 2005;Mussard et al 2007;Leroy et al 2008) or CL quality (Lucy 2001;Wathes et al 2003;Morris and Diskin, 2008;Clemente et al 2009) in the early post-partum period as a reason for increased infertility in dairy herds. It is possible that infectious courses are more important than follicle or CL quality in determining the decrease in fertility in cyclic cows during the post-partum period (Azawi 2008).…”
Section: Discussioncontrasting
confidence: 95%
“…This supports the data of practitioners, who report about adequate breeding success in the early post-partum period, if they breed only cows which show a good heat in that usually nonrecommended time (Beetz 2012). But these results are in contrast to other studies, which identified low follicle (Lopez et al 2005;Mussard et al 2007;Leroy et al 2008) or CL quality (Lucy 2001;Wathes et al 2003;Morris and Diskin, 2008;Clemente et al 2009) in the early post-partum period as a reason for increased infertility in dairy herds. It is possible that infectious courses are more important than follicle or CL quality in determining the decrease in fertility in cyclic cows during the post-partum period (Azawi 2008).…”
Section: Discussioncontrasting
confidence: 95%
“…It is well documented that FSH plays a critical role in bovine follicular development before selection, and is especially closely associated with an alteration of the intrafollicular IGF1 system to promote E 2 production (Rivera & Fortune 2003). Lopez et al (2004) reported that cows that develop multiple dominant follicles show an increase in circulating FSH and E 2 concentrations before follicular deviation. Therefore, although there was no difference in plasma FSH concentrations between the two groups from day K1 to day 2, FSH may contribute to the development of co-dominant follicles.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the basal LH concentration, pulse frequency and AUC of LH were greater in the CL-absent cows than in the CL-present cows during the experimental period. Several studies demonstrated that LH is involved in follicular selection, and that the incidence of co-dominant follicles is closely associated with an increase in the level of circulating LH during the bovine follicular wave (Ginther et al 1998, Kulick et al 1999, Lopez et al 2004. Suppression of LH secretion by P 4 treatment at the time of follicular deviation decreases follicular E 2 and free IGF1 concentrations and increases IGF-binding protein 2 (IGFBP2) concentration in the follicular fluid of the dominant follicle (Ginther et al 2001b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in cows synchronized with the Ovsynch protocol (Fricke and Wiltbank, 1999), double ovulation was much greater in cows that were above average milk production (40.7 kg/day) than below (20.2% v. 6.9%; P < 0.05). Alternatively, analysis of cows with co-dominant follicles during the first follicular wave demonstrated that these cows had greater milk production, lower circulating P4, and a distinct elevation in circulating FSH and LH concentrations during the 24 h before dominant follicle deviation (Lopez et al, 2005a). Thus, greater milk production may produce decreased circulating P4 concentrations due to the increased feed intake and corresponding increases in P4 metabolism.…”
Section: Cellular Mechanisms Regulating P4 Actionmentioning
confidence: 99%